Fate mapping analysis reveals a novel murine dermal migratory Langerhans-like cell population - Jianpeng Sheng; Qi Chen; Xiaoting Wu; Yu Wen Dong; Johannes Mayer; Junlei Zhang; Lin Wang; Xueli Bai; Tingbo Liang; Yang Ho Sung; Wilson Wen Bin Goh; Franca Ronchese; et al. (eLife, 2021)
Dendritic cells residing in the skin represent a large family of antigen-presenting cells, ranging from long-lived Langerhans cells (LC) in the epidermis to various distinct classical dendritic cell subsets in the dermis. Through genetic fate mapping analysis and single-cell RNA-sequencing, we have identified a novel separate population of LC-independent CD207+CD326+ LClike cells in the dermis that homed at a slow rate to the lymph nodes (LNs). These LClike cells are long-lived and radio-resistant but, unlike LCs, they are gradually replenished by bone marrow-derived precursors under steady state. LClike cells together with cDC1s are the main migratory CD207+CD326+ cell fractions present in the LN and not, as currently assumed, LCs, which are barely detectable, if at all. Cutaneous tolerance to haptens depends on LClike cells, whereas LCs suppress effector CD8+ T-cell functions and inflammation locally in the skin during contact hypersensitivity. These findings bring new insights into the dynamism of cutaneous dendritic cells and their function opening novel avenues in the development of treatments to cure inflammatory skin disorders.